ANALYSIS OF THE EFFECTIVENESS AND CONTRIBUTION OF LOCAL TAXES TO THE ORIGINAL INCOME OF BATAM CITY AREA - Candra Simanjorang; Vargo Christian L. Tobing (Jurnal Ekonomi, 2023)
Regional Original Revenue. The central government gives authority to regional governments to manage, promote, and also expand local tax collection in order to create regions that are independent and responsible without relying on the central government. The purpose of this study was to examine the effectiveness and contribution of local taxes to the local revenue of Batam City in 2017-2021. The data analysis method used in this study is a quantitative descriptive analysis method. Quantitative descriptive analysis method is an analytical method that uses financial data calculations to answer problems that are relevant to the research objectives. The level of effectiveness of local taxes in 2017 was 74.13% in the less effective category. In 2018, the level of effectiveness of local taxes was 87.10% in the category of quite effective. In 2019, the level of effectiveness of local taxes was 88.16% in the category of quite effective. In 2020, the level of effectiveness of local taxes is 61.69% in the less effective category. And in 2021, the local tax effectiveness rate is 68.90%. The average local tax contribution in 2017-2021 is 74.91% in the very good category. Regional tax contribution in 2017 was 69.25%. In 2018, local tax contribution was 79.05%. Meanwhile, the regional tax contribution in 2019 was 82.16%. And in 2020 the local tax contribution is 72.81%. And in 2021 the regional tax contribution rate is 71.27%. The average analysis of the effectiveness of local taxes on local revenue for 2017-2021 is 75.99% in the less effective category. And the average analysis of the contribution to local revenue is 74.91% in the very good category.